The problems of international transport corridors development on the territory of the Russian Federation - Rustamzade M. N. (Interactive science, 2017)
in the transition of the leading countries of the world on an innovative way of development, transport is considered as one of the most important factors of socio-economic growth in Russia. Transport contributes to strengthening the unity of the economic area of the country, improves the interregional and international transport and economic relations, increases the efficient using of natural resources, develops entrepreneurship and international cooperation. However, there is a number of obstacles before implementation of transport and transit potential of Russia. The paper deals with features of international and national transport corridors on the territory of Russia and the key problems of their functioning and possible ways to overcome them.
Keywords: железнодорожные перевозки; транспортный коридор; транспортная инфраструктура; transport infrastructure; интермодальные перевозки; международный транзит; transport corridor; intermodal transportation; international transit; railway transportation